Risk Assessment of Occupational Injuries in Underground Coal Mines - Ghosh, Apurna (INSIO Scientific Books and Periodicals, 2010)
Safety is paramount in the underground mining environment. The mining industry has for many years focused on injury prevention at the workplace through procedures and training, and has achieved considerable success. However, the statistics on major accident events and reportable incidents has not shown the corresponding levels of improvement. In the area of major hazards control, the mining industry approach has emphasized mainly on past experiences and lessons learnt. Preventive measures cannot be taken until the causes or sources of accidents are known. Risk management takes care of identifying the sources of accidents. The concept of risk management has come up as an effective tool of accident prevention in mining industry. The objectives of the work are estimation of the risks of different types of job and taking the preventive measures based on the results. Meeting the most recent state-of-the-art safety analysis offers the opportunity to improve product design, reduce accidents, and curb liability exposure. Unfortunately, safety is an issue that sometimes only receives considerable attention after an incident occurs. So far the risk assessment is done in coal mines based on the fatal injuries or disasters as a reactive measure. However, companies that proactively seize the opportunity can minimize the likelihood that an injury event will occur. This work is an endeavour to assess the risk of the reportable injuries of miners as a step of proactive measure.